Optimalisasi Penggunaan Microsoft Word untuk Membuat Surat Bagi Pengelola HIMPAUDI Se Kabupaten Pekalongan - Risqiati, Risqiati; Anas Syaifudin; Sugianti, Devi; Kurniawan, Muhammad Faizal; Setianto, Wahyu (Universitas Methodist Indonesia, 2025)
HIMPAUDI (Association of Indonesian Early Childhood Education and Education Personnel) Pekalongan Regency is an independent organization that brings together elements of educators and education personnel for early childhood. A HIMPAUDI institution is said to be good can be seen from its administrative management in the fields of service, employment, finance and in orderly and regular learning activities. Currently, efficient and effective administrative management is a requirement for every HIMPAUDI institution that exists. The existence of HIMPAUDI management staff who still have difficulty in operating Microsoft Word. Even though in their daily lives the use of computers to manage HIMPAUDI correspondence administration is a mandatory thing to do. Existing limitations such as managers who cannot make mail merges, because so far they have been writing one by one to each recipient of the letter, not knowing how to optimize the buttons on the keyboard or the menus in Microsoft Word to make it easier to create letters are challenges as well as opportunities to carry out community service. Therefore, a community service was carried out to optimize Microsoft Word to create letters for HIMPAUDI administrators and the results obtained after this activity were carried out showed a significant increase from previously 26% of HIMPAUDI administrators who needed a long time to create letters using the toolbar and mail merge to 94% of HIMPAUDI administrators who found it easier to create letters using the toolbar and mail merge.